2018
DOI: 10.1007/s00240-018-1042-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and costs of reusable and single-use flexible ureterorenoscopes: a prospective cohort study

Abstract: The purpose of this study is to analyze clinical outcomes and costs of single-use flexible ureterorenoscopes in comparison with reusable flexible ureterorenoscopes in a tertiary referral center. Prospectively, 68 flexible ureterorenoscopies utilizing reusable (Flex-X2S, Flex-X, Karl Storz) and 68 applying single-use flexible ureterorenoscopes (LithoVue, Boston Scientific) were collected. Clinical outcome parameters such as overall success rate, complication rates according to Clavien-Dindo, operation time and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 29 publications
6
72
0
2
Order By: Relevance
“…When the purchase cost was added to this, a cost of approximately $50 000 per 28 cases was calculated, resulting in a purchase cost of approximately $1500 per disposable fURS to be more economical than reusable fURS . A USA study of 655 fURS also showed similar costings . Our theoretical cost analysis has shown that disposable fURS are more economical for low‐volume centers, although the cost savings diminish over time as more cases are performed.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…When the purchase cost was added to this, a cost of approximately $50 000 per 28 cases was calculated, resulting in a purchase cost of approximately $1500 per disposable fURS to be more economical than reusable fURS . A USA study of 655 fURS also showed similar costings . Our theoretical cost analysis has shown that disposable fURS are more economical for low‐volume centers, although the cost savings diminish over time as more cases are performed.…”
Section: Discussionsupporting
confidence: 58%
“…One study of 34 patients compared the LithoVue with the fiber‐optic URF‐P5/P6 (Olympus) and the digital Flex Xc (Storz, Tuttlingen, Germany), and showed that the LithoVue scored lower on most user comfort and maneuverability scores . Another study of 136 patients showed similar operative outcomes and complications between the Flex Xc/X2S and LithoVue …”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations